The influence of Russian scientists to the methods of teaching literature (Eurasian Journal of Philology Science and Education, 2016)
The article is devoted to studying of problems of Kazakh literature’s teaching. In the researcher the role of artistic work in the development and formations of the person, in progress of his spiritual and moral world, mental potential, character, outlook and attitude is considered. Value of Ibyrai Altynsarin and Ahmet Bajtursynov’s works comes to light. The author marks their contribution to development of a procedure of Kazakh literature’s teaching. The great attention is given to the questions of influence of Russian scientists’ researches on domestic didactics. In the article F.I. Buslaev, V.G. Belinskiy, N.G. Chernyshevskii, V.J. Stojunin, V.P. Ostrogorskii, V.I. Vodovozov’s works are analyzed. On the basis of studying the works of Russian scientists, principles, receptions and features of teaching of the literature are established.
Keywords: literature; a procedure; teaching; training; a science; a method; reception; a principle; influence.